Breaking the norm: An empirical investigation into the unraveling of good behavior - Hill, Ruth Vargas; Maruyama, Eduardo; Viceisza, Angelino (International Food Policy Research Institute, 2010)
We present results from an artefactual field experiment conducted in rural Peru that considers how observing nonreciprocal behavior influences an individual's decision to reciprocate. Specifically, we consider the behavior of second movers in a trust game, assessing how their decision to reciprocate is influenced by the observed behavior of others and the extent to which their actions can be observed. In documenting how an external shock to the number observed not to reciprocate influences reciprocation, the paper endeavors to provide some insight into how reciprocity can unravel when individuals are learning behavior in a new market institution.